Application of fiber optic reflectance spectroscopy for the detection of historical glass deterioration. Issue 1 (31st July 2019) - Zaleski, Stephanie; Montagnino, Elizabeth; Brostoff, Lynn; Muller, Isabelle; Buechele, Andrew; Lynn Ward‐Bamford, Carol; France, Fenella; Loew, Murray
Abstract: Historical alkali silicate glass is prone to deterioration over time due to the uptake of atmospheric water and subsequent hydrolysis of the silicate matrix. Recent studies of historical glass have provided insight into the mechanism of alteration; however, few techniques can assess early onset glass alteration noninvasively. Herein, we present fiber optic reflectance spectroscopy (FORS) as an invaluable tool to analyze historical glass alteration. We study a series of artificially aged model potash glasses and assess the nature of the alkali‐depleted alteration layer by microscopy, scanning electron microscopy (SEM) with energy dispersive spectroscopy, and FORS. We find that the model glass FORS spectra demonstrate peaks associated with hydroxide, liquid‐like water, and bound water. FORS was able to detect an alteration layer as thin as 0.66 µm. The model glass data were then used to generate a hydration thickness prediction curve in order to predict the alteration layer thickness of twenty‐one 19th‐century glass flutes of similar composition. In the one case that an actual flute sample was available, the predicted value was in good agreement with previous SEM measurement. The results indicate the ability of FORS to noninvasively assess glass deterioration and to understand the nature of absorbed water in historical glass objects.